Perbandingan Kandungan Logam Berat pada Sedimen di Kawasan Hutan Mangrove Perancak dan Tahura Ngurah Rai - Yosua Febriyanto; Ima Yudha Perwira; Alfi Hermawati Waskita Sari (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2022)
Mangrove ecosystem is one of the coastal ecosystems which is greatly influenced by human activities around it. The Perancak mangrove forest area has unique characteristics with the condition of its water bodies being influenced by the tides of the Bali Strait. In addition, the Tahura Ngurah Rai mangrove forest area is a mangrove area located in the city center where there are many human activities that can produce household waste, industrial waste and so on. This study aims to determine the heavy metal content of mangrove sediments and the comparison of heavy metal content of mangrove sediments. The method used in this research is descriptive method. Meanwhile, the data collection process was carried out using purposive sampling method. Samples were measured using the spectrophotometric method with the IPC tool. The results of heavy metal measurements in Perancak Mangrove sediments for Pb ranged from 30.3 mg/L and in Tahura Ngurah Rai Mangrove sediments for Pb ranged from 59,9 mg/L. While the heavy metal content of Cd not detecded. Then the heavy metal measurements in Perancak Mangrove sediments for Hg ranges from 11 mg/L and in Tahura Ngurah Rai Mangrove sediments for Pb ranged from 22,1 mg/L . The heavy metal content in the Perancak Mangrove sediment is lower than the heavy metal content in the Ngurah Rai Mangrove sediment.